PENAMBAHAN SATU LANTAI TINGKAT PADA PORTAL GEDUNG BETON BERTULANG TIGA LANTAI - Ali Asroni (Eco Rekayasa: Jurnal Teknik Sipil, 2015)
The aim of this research was to compare three and four floors of reinforce concrete portal design, and the  possibility of the addition of one floor above the three floors building based on building safety. Research was carried out by taking the example of two office building portals constructed in the earthquake zone-one. Both portals were made from the same sketch plan and designed in the full elastic system. The load combinations (dead load, live load, and earthquake load) were subjected to both portals. The loads complied with the Indonesian Code (Tatacara Perhitungan Struktur Beton Untuk Bangunan Gedung, SNI 03-2847-2002). The dimension of portal structures (beam, column, sloof, and foundations) and their reinforcements were properly designed to carry the loads. Based on the dimension of portal and their reinforcement obtained, a comparison could be made up of total reinforcing and spacing of begel on both portals, and the possibility of the addition of one floor above the three floors building. The results showed that the dimensions of the structure (column, sloof, and foundation) of four floors portal were bigger than three floors, had greater number of total longitudinal reinforcement (include of beam), and the begel space of edge beam was more tightly. Moreover, the addition of one floor above the three floors would be dangerous for building safety  and users.